Efficacy of preoperative melatonin versus pregabalin on perioperative anxiety and postoperative pain in gynecological surgeries - Dalia Abdelhamid Nasr; Ayman Ahmad Abdellatif (Egyptian Journal of Anaesthesia, 2014)
Background: We compared the efficacy of melatonin and pregabalin on perioperative anxiety and postoperative pain in patients undergoing laparoscopic gynecological surgeries. Methods: In this randomized double-blind study, 40 patients, 25–35 yr undergoing gynecological surgeries were divided into 2 equal groups to receive either melatonin capsule 6 mg (Group M), or pregabalin capsule 150 mg (Group P) 1 h before induction of general anesthesia. Our primary outcome was preoperative acute anxiety level 1 h after drug administration, 1, 6, and 12 h after operation. The secondary outcomes were postoperative visual analog scale (VAS) for pain, analgesic consumption, sedation level using the inverted observer’s assessment of alertness/sedation scale (OAA/S) scale, and incidence of adverse effects. Results: The anxiety scores decreased significantly >50% after premedication in both groups compared to baseline values (p < 0.01) with no statistically significant difference between the two groups (30.4 ± 4.5 in group M versus 31.7 ± 4.2 in group P, p > 0.05). Postoperative VAS for pain, time for first analgesic demand and number of patients requiring postoperative analgesia did not differ between groups, and the sedation score was higher in melatonin group compared to pregabalin group 1 h after drug (3.45 ± 0.7 versus 1.95 ± 0.6, p < 0.001, respectively) and at all the subsequent readings postoperatively with equal incidence of adverse effects in both groups. Conclusion: Oral melatonin 6 mg or pregabalin 150 mg administered 1 h before operation had reduced perioperative anxiety and postoperative pain in patients undergoing gynecological surgeries, without untoward sedative effects in the pregabalin group compared to melatonin group.